(untitled) (Caring: Indonesian Journal of Nursing Science, 2024)
Cerebral palsy (CP) is a severe mental disorder that affects children. This disease can also lead to activity limitations in brain development, affecting a child’s future intelligence pattern. Musculoskeletal issues, epilepsy, and sensory and behavioral disorders frequently accompany CP motor disorders. The purpose of this study was to explore mothers’ perspectives on caring for children with cerebral palsy at the PNTC Colomadu Clinic. This investigation was qualitative. This investigation included five mothers with children with cerebral palsy and one therapist at the PNTC Colomadu clinic. Interviews, documentation, and observations were implemented to gather data. Data analysis was conducted through data reduction, data presentation, and conclusion. Source triangulation, method triangulation, and technique triangulation were implemented during the data validity assessment. 1) The findings indicate that cerebral palsy children require ongoing therapy and learning. 2) Children with cerebral palsy require learning, affection, and nurturing tailored to their unique requirements. 3) The goal of therapy is for the child to become independent. The CP advises parents to anticipate parental cooperation and family contribution to continue the development of abilities and provide children with education and enthusiasm.